Cavitation Mediated 3D Microstructured Architectures from Nanocarbon. (25th March 2018) - Zhang, Zishuai; Ye, Siyu; Gbureck, Uwe; Barralet, Jake E.; Merle, Géraldine
Abstract: Here, the formation of high surface area microscale assemblies of nanocarbon through phosphate and ultrasound cavitation treatment is reported. Despite high conductivity and large surface area, potential health and safety concerns limit the use of nanocarbon and add challenges to handling. Previously, it is shown that phosphate ultrasonic bonding is ineffective for organic materials but in this study, it is found that by a preliminary oxidizing treatment, several carbons can be readily assembled from xerogels. Assembling nanocarbon into microparticles can usually require a binder or surfactants, which can reduce surface area or conductivity and generate a low microsphere yield. Carbon nanotube microspheres are nitrogen‐doped and flower‐like nanostructured Pt deposited on their surface, and finally showcased as efficient cathode electrocatalysts for the oxygen reduction reaction (half‐wave potential 0.78 V vs reversible hydrogen electrode) and methanol oxidation (417 mA mg −1 ). In particular, no significant degradation of the catalysts is detected after 12 000 cycles (26.6 h). These results indicate the potential of this multimaterial assembly method and open a new way to improve handling of nanoscale materials. Abstract : Cavitation induced 3D microstructured microspheres from nanocarbon ultrasonically bonded into higher dimensional architectures are formed and used as catalytic supports. Apart from reducing health issues associated with nanoscale materials, these durable microspheres can be readily used in energy sector without compromising the surface area and conductivity.